Evaluating the effect of brand equity and its implications on customer lifetime value. a case of nebula agencies trading as Fabs hardware, Westgate, Harare. - Mamombe, Jeraldine (Midlands State University, 2017)
The research was carried out to evaluate the effect of brand equity and its implications on customer lifetime value. Research was based on Nebula agencies trading as FABS hardware in Westgate, Harare. The objectives for the research were; to evaluate the effect of brand equity on customer lifetime value, effect of brand association on customer lifetime value and the effect of brand loyalty on customer lifetime value. The research covered the period from January to December 2015. Both exploratory and descriptive research designs were used to collect data for the study. The researcher also made use of judgemental and convenience sampling techniques to select participants of the research. Both secondary and primary data was used to gather first-hand information through administering questionnaires and conducting interviews, and company sales reports and customer accounts databases. Population used for the branch consisted of 2000 elements. The sample size used by the researcher comprised of 100 customers and 6 employees and management. The research instruments that were used in data collection were interviews and questionnaires. Data was collected at Westgate complex in Harare through questionnaires distributed in and around FABS hardware. The data collected was analysed and presented through use of tables, graphs and charts. The findings from the research highlighted that, brand equity is effective in enhancing customer lifetime value for FABS hardware. The findings showed that brand awareness, association and loyalty for FABS hardware had affected customer lifetime value. The researcher went on to conclude that FABS hardware does not hold strong brand equity and this has affected customer lifetime value. The researcher recommends that FABS could strengthen brand equity elements in order to benefit from higher customer lifetime value and sales. The researcher also recommended FABS hardware to full utilise marketing tools such as, advertising and online marketing to increase brand equity. Further research must be done on the effect of brand equity on company profitability.